An analysis of trinities in Ali Shariati's speeches / Fatemeh Moghaddam - Fatemeh , Moghaddam (2017)
In the recent decades, Shariati’s influence in the realm of social sciences and Iranian revolution of 1979 has been debated in academic circles and beyond. However, the body of scholarship on his unique use of language in his political rhetorical discourse is yet to be enriched. The existing literature about Shariati only mention the important influence of his famous phrase 'the trinity of wealth, oppression, hypocrisy ' which is 'taslis e zar, zur, tazvir' in Persian. However, the present study asks if there are other similar structures that he calls a trinity in his work and if so whether these stylistic and artful usage of language are only ornaments of his prose or are in the service of his political concerns. Therefore, this is an attempt to tease out Shariati’s socio-political concerns expressed through what he calls a trinity. As a result, fifty-six cases of the usage of the term 'trinity' were studies and while one trinity is well mentioned in the existing literature six more trinities were found through this research. Using the rhetorical analysis framework of Corbett & Connors (1999), the schematic figures of speech applied in these trinities were identified and analyzed. This study shows that there are various figures of speech used in these seven specific trinities the most important of which is that they are all tricolons. The findings also demonstrate that there is a one for one synonymous relationship between three elements used in all seven tricolons in a way that they all represent the same theme of exploitation of the public through political, economic or religious power. Therefore, Shariati did not solely use the figure of speech of tricolon and other sonic and schematic figures of speech as stylistic features to coin poetique catch phrases like ''zar, zur, tazvir, but rather he meticulously creates these seven trinities as an indirect way to deliver his political messages while being under surveillance by the Iranian intelligence agency (SAVAK) during the second Pahlavi king (Mohammad Reza Pahlavi).